Copper-Catalyzed NaBAr4-Based N-Arylation of Amines - Yang, Qin; Lei, Xiaoli; Yin, Zhijian; Deng, Zhihong; Peng, Yiyuan (Synthesis, 2019)
Using NaBAr4 as an arylating agent, the formation of carbon–heteroatom bonds by a Cham–Lam cross-coupling reaction in the presence of catalytic copper(II) acetate monohydrate in acetonitrile at room temperature under air is described. The investigation of reaction scope suggests that several aliphatic and aromatic amines are compatible. In particular, the reaction of alkylamine and NaBAr4 proceeds smoothly to offer the corresponding products in good to excellent yields.
Keywords: Cham–Lam cross-coupling reaction; amine; copper acetate monohydrate; tetraphenylborate; N-phenylation